Evaluation Anxiolytic Effect of Methanol Extract of Ceplukan Leaves (Physalis minima L.) in the Elevated Plus Maze Test through IL-6 Level Changes in Ovariectomized Rats - Nurfitria, Siti; Permatasari, Nur; Ratnawati, Retty (Journal of Tropical Life Science, 2015)
Ceplukan (Physalis minima L.) has long been used to treat various conditions in traditional medicine. This study aims to demonstrate the anxiolytic effects of Methanol Extract of Ceplukan Leaves (MECL) in the Elevated Plus Maze (EPM) test and correlate to IL-6 level of ovariectomized rat brain. Total of 24 Wistar rats were divided into six groups: one normal group, one group of 1 month ovariectomized (ovx), one group of 2 months ovx, three groups of 2 months ovx (each given with MECL 500; 1500 and 2500 mg/kg doses for 1 month). The anxiety-like behavior level was measured by EPM test. After EPM test, the brain was removed to measure level of IL-6 by ELISA. The data were processed and analyzed by one-way ANOVA and Pearson correlation. We found that the MECL-treated rats enter the opened-arm higher than the control rats. It indicates that the MECL-treated rats are less anxious than the control rats. The results also show the decreased of IL-6 level in MECL-treated rats.